The Relationship of Smartphone Use to Adolescent Sleep Quality in SMKN 1 Pandeglang - Alfu, Nadia Nur; Suartini, Endang (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
Background: The future of a nation will be determined by its youth today. Because adolescents are its greatest asset. Adolescents encounter health issues at this developmental stage. Another important adolescent health problem is the lack of fulfillment of sleep quality in adolescents. One of the causes of poor sleep quality in adolescents is the excessive use of smartphones. Purpose: The aim of this study was to find out whether cell phone use and sleep quality among young adults are linked. Methods: This kind of study is cross-sectional comparative analytic research. 95 respondents were remembered for the purposive testing test utilized in the examination. The research instrument used in this study is the Smartphone Addiction questionnaire, which is a measuring instrument used to measure smartphone use using a measuring instrument that has been modified and tried out by Nurdiani's research (2015) and the Pittsburgh Sleep Quality Index (PSQI) which has been developed by Contreras et al., (2014). Results: The results of the Chi-Square test obtained a P Value of 0.002 less than the significant value (a=0.05). Conclusion: This study shows that smartphone use and sleep quality in adolescents are linked. Suggestion: it is hoped that adolescents can reduce excessive use of smartphones so as not to have a more severe impact, especially on sleep quality and it is hoped that adolescents can manage sleep time properly so that there is no decrease in sleep quality.